MOTIVASI, KEPUASAN, PERSEPSI IMBALAN PERSEPSI SUPERVISI DAN KINERJA DOSEN - Aprilina, Vita (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
The purpose of this study is to determine the effect of work motivation, job satisfaction, perceptions of rewards and perceptions of supervise affect the performance of lecturers in implementing teaching and learning process at Universitas Islam "45" Bekasi.While, the data in this study were obtained through questionnaires given to the lecturers who remained in the environment of Universitas Islam "45" Bekasi. From a sample of 101 questionnaires distributed to permanent lecturers in Universitas Islam?45? Bekasi, only 34 questionnaires were returned, then analyzed by multiple regression techniques. Based on the result of the questionnaires collected can be disclosed that work motivation and reward perception have a significant positive effect on the performance of lecturers in implementing teaching and learning process, while job satisfaction and perception of supervision does not affect the performance of lecturers in implementing the learning process in Universitas Islam "45" Bekasi.